2022
DOI: 10.1038/s41467-022-35171-y
|View full text |Cite
|
Sign up to set email alerts
|

Insights into magma ocean dynamics from the transport properties of basaltic melt

Abstract: The viscosity of magma plays a crucial role in the dynamics of the Earth: from the crystallization of a magma ocean during its initial stages to modern-day volcanic processes. However, the pressure-dependence behavior of viscosity at high pressure remains controversial. In this study, we report the results of first-principles molecular dynamics simulations of basaltic melt to show that the melt viscosity increases upon compression along each isotherm for the entire lower mantle after showing minima at ~6 GPa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 107 publications
(223 reference statements)
4
15
0
Order By: Relevance
“…While the slope of Fe 2+ ‐bearing MgSiO 3 glass is 8% less than pure MgSiO 3 (Mashino et al., 2022; Murakami & Bass, 2011), 20.5 mol% of Al 2 O 3 ‐bearing SiO 2 glass shows almost 14% higher slope with respect to simplest SiO 2 glass (Murakami & Bass, 2010; Ohira et al., 2016) after the inflection pressure,which is evident that Al could make SiO 2 glass much stiffer with pressure. Our results support that Al acts as network former and undergoes the higher coordination (>6 + ) at much lower pressure than Si as predicted by various studies for different glasses/melts (Bajgain et al., 2015, 2022; Ghosh & Karki, 2018; Ohira et al., 2019; Solomatova & Caracas, 2019). So we could assume that when the pressure is increased from the inflection point, the fraction of 6 + in (Fe, Al)‐silicate glass is expected to increase faster than in MgSiO 3 glass because Si undergoes a CN change following Al, and Fe 2+ .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While the slope of Fe 2+ ‐bearing MgSiO 3 glass is 8% less than pure MgSiO 3 (Mashino et al., 2022; Murakami & Bass, 2011), 20.5 mol% of Al 2 O 3 ‐bearing SiO 2 glass shows almost 14% higher slope with respect to simplest SiO 2 glass (Murakami & Bass, 2010; Ohira et al., 2016) after the inflection pressure,which is evident that Al could make SiO 2 glass much stiffer with pressure. Our results support that Al acts as network former and undergoes the higher coordination (>6 + ) at much lower pressure than Si as predicted by various studies for different glasses/melts (Bajgain et al., 2015, 2022; Ghosh & Karki, 2018; Ohira et al., 2019; Solomatova & Caracas, 2019). So we could assume that when the pressure is increased from the inflection point, the fraction of 6 + in (Fe, Al)‐silicate glass is expected to increase faster than in MgSiO 3 glass because Si undergoes a CN change following Al, and Fe 2+ .…”
Section: Discussionsupporting
confidence: 90%
“…In fact very recent spin polarized calculations on pyrolite melt, the average CN of Fe‐O reaches 6 above 25 GPa and in the core‐mantle boundary (CMB) conditions it is 6–7 (Solomatova & Caracas, 2019). One experimental study on the Al 2 O 3 ‐SiO 2 glass showed an average Al‐O CN increase from 4 to 6 above 20 GPa, and from 6 to >6 ∼110 GPa (Ohira et al., 2019), while theoretical calculations on the model basaltic melt, pyrolite glass and melt a gradual increase is predicted with higher than 6 CN in the pressure range 60–80 GPa (Bajgain et al., 2015, 2022; Ghosh & Karki, 2018; Solomatova & Caracas, 2019) and reaching 7 toward the CMB conditions. It is therefore evident that both Fe‐O and Al‐O undergo the higher CN much earlier than Si‐O and have a large effect on the reduction of the inflection pressure.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we speculate that, upon decompression, melt polymerization may occur as a result of pressureinduced oxidation of Fe 2+ to Fe 3+ and the subsequent transition of Fe 3+ modifier to Fe 3+ O 4 5− former as Fe 3+ CN decreases, and that this melt polymerization should result in an increase in viscosity. Independent evidence for this comes from other AIMD simulations on basaltic melts, in which such liquids, at 2200 K, exhibit decreasing viscosities up to Frontiers in Earth Science frontiersin.org ~10 GPa before undergoing a drastic increase above these pressures (Bajgain et al, 2022). Such hypothesis is also in accord with the conclusions of Spice et al (2015).…”
Section: Structural Role Of Iron In Peridotite Glassessupporting
confidence: 53%
“…In contrast, low-viscosity melts form wide, shallow intrusions, such as sills and laccoliths. The melt viscosity also influences the intrusive patterns, e.g., multiple parallel dikes in case of highviscosity, whereas large, single intrusives for low-viscosity conditions (Bajgain et al, 2022;Petford et al, 2000;Tobias Schmiedel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%